BEING AN AUTHOR UNDER THE ROMANIAN COMMUNIST REGIME. THE ACTIVITY OF EDITOR-IN-CHIEF ION BRAD FOR THE RED TIE (1956-1958) - CISTELICAN, Mihai (Studia Universitatis Babeș-Bolyai Ephemerides, 2018)
He witnessed the foundation of the Communist regime in Romania and lived nearly all his life under socialism. The Romanian author Ion Brad is one of those who observed from the inside how the socialist regime propagated its beliefs in the media among the population. For almost 70 years, Ion Brad published hundreds of articles in communist newspapers and magazines such as The Literary Almanac, The Star, The Red Tie, The Pioneer’s Spark, The Literary Gazette and others. The present study is meant to cover the activity of editor-in-chief Ion Brad for the children’s magazine The Red Tie in a period of time when Communism was just taking up the reins in Romania (1956-1958). Apart from the articles he published, we also wanted to analyse the context in which he had to work (his collaboration with other authors, topics promoted in the magazine etc.). This study could prove very handy for future research in terms of better understanding how Ion Brad rendered the reality in the press of the time and also in observing the context in which writers did their job in a country from Eastern Europe, where Communism had already taken control for 10 years, in the time of a Cold War between two political and ideological systems.